Synthesis of (5-Iminio-4,5-dihydro-1,3,4-oxadiazol-2-yl)tetrazol-1-ide: A Zwitterionic Compound Containing a Tetrazole Anion as a Promising Blunt Energetic Material - Liu, Yaxin; Lv, Meifang; Zhang, Guofeng; Ye, Zhiwen (Synthesis, 2024)
(5-Iminio-4,5-dihydro-1,3,4-oxadiazol-2-yl)tetrazol-1-ide is the first zwitterionic energetic material containing tetrazole as an anion and 1,3,4 oxadiazole as a cation. Its low mechanical sensitivity (IS >40 J, FS >360 N) and high gas volume after detonation at standard temperature and pressure (767.0 dm3/kg) make it a prime example of a novel type of blunt energetic material with promising applications.
Keywords: zwitterionic compounds; tetrazole; 1,3,4-oxadiazole; energetic materials; low mechanical sensitivity